Use some environmentally safe control factors in the fight against Sesamia cretica. Led (Phalaenidae: Lepidoptera). - Othman Hussein Ali al-Rafi'i,,; Abd al-Baqi al-Sayyid Ali,; Saif al-Din Muhammad Khair,; Muhammad Zaidan Khalaf, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
Laboratory experiments have been carried out on the effectiveness of someenvironmentally safe control factors in the fight against the Sesamia cretica Led. For thispurpose, pesticide preparations are used: bacillus thuringiensis, Beauveria bassianamushrooms and pesticides of natural origin: Neem extract, Levo 2.4 LS, Matrixine Plus,Actra and three different concentrations each, laboratory and field experiments werecompleted during the spring and autumn 2019.The results of laboratory experiments indicated that biopesticide preparations gave a killrate in the larvae of the corn stalk stalk s. cretica: 88%, 96% for each of the bacteria B.thuringiensis mushroomB. bassiana respectively when used at 6 ml/l water when used indirect spraying on larvae. Pesticides of natural origin gave a kill rate of 80%, 80%, 88%and 100% for both neem, matrixin esauce, atara and livo, respectively, when used at 1mlper liter of water when used in direct spraying on larvae. When using these factors in anindirect treatment (larval food treatment), the results indicated that biopesticidepreparations decreased slightly compared to their direct spraying method on larvae andreached: 64%, 72% for each of the bacteria B. thuringiensis mushroom B. bassiana,respectively, Pesticides of natural origin have been effective: 68%, 96%, 100% and 100%each for neem, livo, matrixen plus and alektara, respectively. From the results obtainedfrom the research, the above control factors can be used as part of an integrated controlprogram by controlling the S. cretica corn stem excavator after the completion of its fieldeffective test.